2018
DOI: 10.3389/fphys.2018.00398
|View full text |Cite
|
Sign up to set email alerts
|

Intercalated Disk Extracellular Nanodomain Expansion in Patients With Atrial Fibrillation

Abstract: Aims: Atrial fibrillation (AF) is the most common sustained arrhythmia. Previous evidence in animal models suggests that the gap junction (GJ) adjacent nanodomain – perinexus – is a site capable of independent intercellular communication via ephaptic transmission. Perinexal expansion is associated with slowed conduction and increased ventricular arrhythmias in animal models, but has not been studied in human tissue. The purpose of this study was to characterize the perinexus in humans and determine if perinexa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 45 publications
4
40
0
Order By: Relevance
“…The experienced user found that W p was significantly wider in patients with AF than without AF (21.9±2.5 and 18.4±2.0 nm, respectively, Figure 9 A ). These values with the correction factor applied are similar to those reported previously (24.4±2.2 nm and 20.7±2.4 nm, respectively) 6 . Importantly, the inexperienced user found the same significant difference (22.1±2.8 nm and 20.1±2.6 nm, respectively) between disease states with the automated program.…”
Section: Representative Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…The experienced user found that W p was significantly wider in patients with AF than without AF (21.9±2.5 and 18.4±2.0 nm, respectively, Figure 9 A ). These values with the correction factor applied are similar to those reported previously (24.4±2.2 nm and 20.7±2.4 nm, respectively) 6 . Importantly, the inexperienced user found the same significant difference (22.1±2.8 nm and 20.1±2.6 nm, respectively) between disease states with the automated program.…”
Section: Representative Resultssupporting
confidence: 91%
“…The quantification of the GJ-adjacent perinexus nanodomain width (W p ) is typically accomplished by manual segmentation. This manual segmentation process is demonstrated in Figure 1 A and was described previously 6 . The observer identifies the edge of the GJ ( Figure 1 , red dot), measures 5nm along the center of the perinexus, and measures the distance between the membranes at that point.…”
Section: Representative Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, in long QT syndrome type 3 (LQT3; a disorder stemming from pathological gain of Na V 1.5 function), the Poelzing group recently demonstrated that transient depletion of extracellular Na + within perinexal nanodomains may mitigate risk of premature beats, and that perinexal widening may unmask the latent arrhythmia risk ( Greer-Short et al, 2017 ). More recently, they have demonstrated that wider perinexi associated with the occurrence of AF in human patients ( Raisch et al, 2018 ). While these are early days yet, these results collectively support the view that ultrastructural alterations within Na V 1.5-rich nanodomains may be a key determinant of arrhythmia risk, and therefore, a potential target for antiarrhythmic therapy.…”
Section: The Nano-machinery Of Cardiac Electrical Excitationmentioning
confidence: 99%